The queering of the apparel industry: Exploring transgender consumer needs when shopping for clothing. Issue 2 (1st May 2021) - Nelson, Audrey L.; Hwang, Chanmi
For individuals who identify as queer, the concept of 'men's' and 'women's' clothing departments is often not ideal and does not align with their values, role or body image. This study explores transgender consumers' experiences and needs when shopping for clothing and provides suggestions on how apparel retailers can promote a more inclusive apparel shopping experience. Four themes surfaced as participants in this study discussed their apparel shopping experiences: (a) inclusivity throughout store layout and interaction with retail sales staff, (b) gender-affirming clothes that positively influence role and self-esteem, (c) non-restrictive garment fit and compression, and (d) interest in inclusive androgynous styles and aesthetic qualities from queer artists to benefit the queer community. In this study, the concept of trans-inclusive is used as a way of welcoming and implementing the idea of apparel and fashion beyond cisnormative identities, and also as a way to advocate for inclusivity in all consumer markets. This research provides insights for the apparel industry on what is needed for this emerging market of queer individuals and promotes a more inclusive apparel shopping experience.